Anomalous quantization trajectory and parity anomaly in Co cluster decorated BiSbTeSe2 nanodevices. Issue 1 (December 2017) - Zhang, Shuai; Pi, Li; Wang, Rui; Yu, Geliang; Pan, Xing-Chen; Wei, Zhongxia; Zhang, Jinglei; Xi, Chuanying; Bai, Zhanbin; Fei, Fucong; Wang, Mingyu; Liao, Jian; et al.
Abstract Dirac Fermions with different helicities exist on the top and bottom surfaces of topological insulators, offering a rare opportunity to break the degeneracy protected by the no-go theorem. Through the application of Co clusters, quantum Hall plateaus were modulated for the topological insulator BiSbTeSe2, allowing an optimized surface transport. Here, using renormalization group flow diagrams, we show the extraction of two sets of converging points in the conductivity tensor space, revealing that the top surface exhibits an anomalous quantization trajectory, while the bottom surface retains the 1/2 quantization. Co clusters are believed to induce a sizeable Zeeman gap ( > 4.8 meV) through antiferromagnetic exchange coupling, which delays the Landau level hybridization on the top surface for a moderate magnetic field. A quasi-half-integer plateau also appears at −7.2 Tesla. This allows us to study the interesting physics of parity anomaly, and paves the way for further studies simulating exotic particles in condensed matter physics. The topological surface states usually appear in pairs in a topological insulator, with one on the top surface and the other on the bottom surface. Here, Zhang et al. utilize Co cluster to induce a Zeeman gap on one surface through antiferromagnetic exchange coupling, and observe a quasi-half-integer plateau, suggesting the parity anomaly of Dirac fermions.